A Study on R. K. Narayan’s Use of Myth in His Fictions: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper attempts to show to the reading public that R.K. Narayan is a prolific writer with an ambition to prove a prominent modern writer creating a fictional world the immense mythical dimensions following the puranic pattern rendering the ancient myth with credibility of using both parallelism and ironic contrast and projects Narayan as an outstanding writer dealing richly with use of myths and symbols in his novels.